Autonomous robotic system for high-efficiency non-destructive bridge deck inspection and evaluation - La, Hung M.; Lim, Ronny S.; Basily, Basily; Gucunski, Nenad; Jingang Yi; Maher, Ali; Romero, Francisco A.; Parvardeh, Hooman (2013 IEEE International Conference on Automation Science and Engineering (CASE), 2013)
Bridges are one of the critical civil infrastructure for safety of traveling public. The conditions of bridges deteriorate with time as a result of material aging, excessive loading, and inadequate maintenance, etc. In this paper, the development of an autonomous robotic system is presented for highly-efficient bridge deck inspection and evaluation. An autonomous mobile robot is used as a platform to carry various non-destructive evaluation (NDE) sensing systems for simultaneous and fast data collection. Besides the NDE sensors, the robot is also equipped with various onboard navigation sensors. A sensing integration scheme is presented for high-accuracy robot localization and navigation. The effectiveness of the autonomous robotic NDE system is demonstrated through extensive experiments and field deployments.